If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -4) + 5(x + 5) = 0 Reorder the terms: 4(-4 + x) + 5(x + 5) = 0 (-4 * 4 + x * 4) + 5(x + 5) = 0 (-16 + 4x) + 5(x + 5) = 0 Reorder the terms: -16 + 4x + 5(5 + x) = 0 -16 + 4x + (5 * 5 + x * 5) = 0 -16 + 4x + (25 + 5x) = 0 Reorder the terms: -16 + 25 + 4x + 5x = 0 Combine like terms: -16 + 25 = 9 9 + 4x + 5x = 0 Combine like terms: 4x + 5x = 9x 9 + 9x = 0 Solving 9 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 9x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 9x = 0 + -9 9x = 0 + -9 Combine like terms: 0 + -9 = -9 9x = -9 Divide each side by '9'. x = -1 Simplifying x = -1
| 2x(10x+24)=180 | | (1-3y)3= | | B=x-x^2 | | 5-x-5=26 | | 18-5= | | (T+5)(t+9)-6(t+6)= | | x^2+20x-19=0 | | x^4+15x^2+50=0 | | (x^3)(x^2-4x+4)=0 | | u=4(9n+32)+7(n+1) | | y=-3x^3+7x^2-5 | | -7(4*-0.5+2)=5(2*-0.5+1) | | (x-5)=0,66 | | 2x+3x+5=13 | | 15x+19=34 | | 0.9x-4.9=0.5 | | 9x-5=9(x-4) | | -3y+11=-2(3y+8) | | 20x-8=45x+2 | | 5(1-x)=-3(x-3)+2x | | (2y+9)(4y-6)=180 | | 3(x-6)=1+4x | | 2-w=-18 | | 3y+20=44 | | -4b+12=24 | | 34(x)-21(1-x)=0 | | 2h-7=h-13 | | 34(x)-140(1-x)=0 | | 34(x)-120(1-x)=0 | | ((200)(0.6)(1-x))+((22+9+3)(x))=0 | | 35*-6+12=40*-6+42 | | 11*-28-23=12*-28+5 |